The impact of dual HIV and HPV vaccine strategies among adolescents in a resource constrained setting - Moodley, Nishila (My University, 2017)
Introduction With the largest epidemic in the world, the consequences of human immunodeficiency virus (HIV) in South Africa extend far beyond its disease burden. In fact, patterns of HIV-related infection and mortality in South Africa still reflect social cleavages and inequalities. Similarly, poverty-related issues such as poor education, unemployment and subsequent low socio-economic status, rural residence and inadequate access to health care are all implicated in human papillomavirus (HPV) associated cervical cancer-related mortality (of which South Africa also has the highest globally). Despite the knowledge of reproductive functions and sexuality being poor among adolescents in South Africa, the majority commence their sexual activity early with an estimated national average of 15 years for girls and 14 years for boys. Further, many South African adolescents engage in sexual risk-taking behaviours including concurrent partners and unprotected sexual acts that considerably increase their vulnerability to sexually transmitted infections including HIV and HPV. In recognising the unique health needs of adolescents in South Africa, the national government has already pin-pointed school health services as a strategic arm of primary health care re-engineering. The aim of this body of work is to elaborate on restructuring of adolescent health care by introducing the HIV and HPV vaccine concomitantly in South Africa via a school-based sexual and reproductive health service. Methodology Data from four studies were analysed and are presented in three published and two unpublished papers. The first study evaluated the synergism between HIV and HPV in the South African context and formed the basis of the literature review. The second study considered HIV vaccine implementation alone. The third study assessed dual HIV and HPV vaccine strategies among females and the final study compared the dual vaccination strategy against recognised biomedical HIV prevention interventions. The studies evaluated the implementation of a hypothetical HIV vaccine and the bivalent HPV vaccine both individually and in combination when administered to school-going adolescents in South Africa. The health outcomes and the cost-effectiveness of these strategies were assessed. Assumptions were made regarding the hypothetical HIV vaccine (based on HIV vaccine studies conducted to date) including a coverage rate of 60% (uncertainty range: 30-70%), vaccine efficacy of 50% (uncertainty range: 30-70%) and vaccine price per dose of US$ 12 (uncertainty range: US$ 3-24). The uncertainty ranges were tested in the sensitivity analysis. Mortality statistics, disease transition parameters (for the individual diseases and the models representing joint disease) and HPV vaccine characteristics were drawn from the South African literature. The joint effectiveness of the dual vaccine strategy was considered multiplicative. Nine year old adolescents attending South African schools in 2012 were eligible for the intervention (vaccination) that was introduced opportunistically as part of the national health initiative introducing school-based sexual and reproductive health services. The learners were targeted prior to their reported sexual debut. The HIV vaccine was considered against the comparator of HIV counselling and testing (HCT) and the national roll-out of antiretroviral therapy (ART) that constituted the standard of care in South Africa. The HPV vaccine was modelled as prevention against HPV-related cervical cancer and pre-cancerous HPV-related cervical states. The health service provider (provider) perspective was adopted and the cohort was modelled through a lifetime horizon of 70 years with annual cycles. The economic costs and health outcomes were discounted at 3% with an uncertainty range between 0% and 6% assessed. Cost valuations were for 2012 and costs were adjusted to this common year. The quality-adjusted life year (QALY) was used as the outcome measure of health related quality of life and was used to calculate the incremental cost-effectiveness ratio (ICER) of the comparator against the vaccination interventions. The core model was a semi-Markov simulation with annual cycles. The study population entered the model HIV and HPV disease free and were exposed to the risk of acquiring each disease annually. The model structure was parameterised drawing from South African data available in the literature. One-way sensitivity analyses evaluated the impact of single assumptions on cost and outcomes. Probabilistic sensitivity analysis (PSA) with a bootstrapping technique explored the uncertainty in the model and evaluated the robustness of the results. The PSA data generated determined if the intervention fell below the willingness-to-pay (WTP) threshold. As South Africa does not have a pre-defined WTP threshold, the Gross Domestic Product (GDP) per capita (for 2012) was used as a proxy in accordance with the World Health Organization’s Guide to Cost-Effective Analysis. Additionally, benchmark interventions were used in the final comparison study as a measure of cost-effectiveness. Ethical approval for the study was obtained from the Human Research Ethics Committee (Medical) of the University of the Witwatersrand. Findings The second study explored the implementation of the HIV vaccine on an individual and national, programmatic level. The simultaneous implementation of HIV vaccination services with current HIV management programmes would be cost-effective, even at relatively higher vaccine cost. At base vaccine cost of US$ 12, the ICER was US$ 43 per QALY gained, with improved ICER values yielded at lower vaccine costs. The ICER was sensitive to the duration of vaccine-mediated protection and to variations in the vaccine efficacy. Data from this work demonstrate that vaccines offering longer duration of protection and at lower cost would result in improved ICER values. Assessing this HIV vaccine model on a national programmatic level, yielded an ICER of US$ 5 per life-year gained (LYG) (95% CI US$ 3-12) compared with the comparator. This fell considerably below the national WTP threshold of cost-effectiveness. This also translated to an 11% increase in per capita costs from US$ 80 to US$ 89. National implementation of this intervention could potentially result in an estimated cumulative gain of 24 million years of life (95% CI 8–34 million years) among those adolescents aged between 10-19 years that were vaccinated. The 10 year absolute risk reduction projected by HIV vaccine implementation was 0.42% for HIV incidence and 0.41% for HIV mortality. The ICER was sensitive to the HIV vaccine efficacy, coverage and vaccine pricing in the sensitivity analysis. The third study assessed the impact of dual HIV and HPV implementation strategies. Programmes that involved the dual vaccine strategy were assessed as cost-saving. ICER values were sensitive to the HIV vaccine cost. The dual vaccine strategy resulted in 10 year absolute risk reductions in HIV incidence (5.24%), dual mortality (1.21%) and a reduction in HPV incidence (0.39%) compared with no vaccination. Importantly, the reduction in HIV incidence rate and dual mortality rate in the dual vaccine strategy exceeded the reductions noted with the use of the HIV vaccine alone. All scenarios assessed with the dual vaccine strategy were cost-effective. Lower vaccine prices and reduced discount rates were associated with improved ICER outcomes. The final study compared the biomedical interventions of oral pre-exposure prophylaxis (PrEP), voluntary medical male circumcision (VMMC) and the scaling-up of ART coverage against the vaccine strategies. When compared with other biomedical HIV prevention interventions, the dual vaccination intervention was the most cost-effective strategy (US$ 7 per QALY gained) and averted 29% of new HIV infections. VMMC (US$ 30 per QALY gained) proved more cost-effective than HIV vaccination alone (US$ 93 per QALY gained), though VMMC averted 6% more new infections than the HIV vaccine. PrEP interventions were the least cost-effective. Combined dual vaccination and VMMC strategies represent the only dominant intervention. Strategies involving oral PrEP were the least cost-effective. Conclusion The findings of this thesis have implications for school-based adolescent health care and HIV- and HPV-related disease prevention among adolescents, a highly susceptible population. The cost-effectiveness of the dual HIV and HPV vaccine strategy was demonstrated, and the improved health outcomes associated with the interventions quantified. Proposals were suggested regarding possible combinations of HIV prevention interventions that could yield the favourable health outcomes with the most efficient use of financial resources. Several important areas for future research were identified to shed light on improving adolescent health care and for optimising HIV prevention strategies. These include integrating HIV and HPV services as part of the re-engineering of primary health care in South Africa, and then formulating economic evaluations of HIV/HPV prevention strategies targeting adolescents specifically. Further, more effective methods of collecting data on socially marginalised populations such as young people need to be explored. Another vital research area is the discussion and implementation of existing school health documents with the ideals embodied in the school health programme envisaged under the National Health Insurance restructuring. Once these are integrated, the cost implication of the combined programmes need to be assessed.
A thesis completed by published work, Submitted to the School of Public Health, Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy Johannesburg, South Africa December 2016.
Keywords: HIV; Papillamaviridae; Uterine Cervical Neoplasm--prevention & control; Genital Diseases, Female